(untitled) (Biomedical Research and Therapy, 2021)
The incidence of Osler–Weber–Rendu disease is low, ranging from 1 detected case per 50,000 to 1 per 100,000 population. The disease is hereditary, with autosomal dominant transmission, caused by pathogenic mutations in genes involved in angiogenesis. The disease has a pronounced clinical picture of multiple telangiectasias of the skin and mucous membranes and manifests as spontaneous bleeding. This scientific article presents a clinical analysis of a 65-year-old patient with a diagnosis of Osler–Weber–Rendu disease. Early identification of the manifestations of this disease and careful observation of the patient give a favorable prognosis of the course and prevent the development of severe complications.